Nocturnal Scratching and Quality of Sleep in Children with Atopic Dermatitis - Akiko Sugiyama; Yoko Murakami; Kazuaki Okamoto; Hiroshi Nakano; Masatoshi Wakatsuki; Toshiaki Kawano; Yuko Akamine; Mihoko Iwata; Chikako Motomura; Kaoru Kojima; Makiko Oda; Satoshi Honjo; et al. (Acta Dermato-Venereologica, 2023)
Itching due to atopic dermatitis causes sleep disorders in children, but its pathology is unknown. The aim of this study is to investigate nocturnal scratching as an indirect index of itching during sleep and its relationship with depth of sleep in children with atopic dermatitis. Nocturnal scratching was measured in a total of 20 children with atopic dermatitis, using a smartwatch installed with the application Itch Tracker. Depth of sleep was analysed using polysomnography. The severity of atopic dermatitis was scored using Eczema Area and Severity Index (EASI) and Patient-Oriented Eczema Measure (POEM). The number and time of nocturnal scratching measured by Itch Tracker had a significantly positive correlation with EASI scores, whereas POEM scores were not correlated with EASI scores. Mean sleep efficiency was 90.0% and scratching episodes (n = 67) started mainly during the awake stage or light sleep stages. In the scratching episodes that started during sleep stages (n = 34), the sleep stage changed to a lighter one or to the awake stage in 35.5% of episodes. Itch Tracker is applicable to measure nocturnal scratching in children. Nocturnal scratching can deteriorate quality of sleep by changing the sleep stage to a lighter one or to the awake stage.